Composição e comportamento de um consórcio composto por microalgas e bactérias em reatores biológicos do tipo aberto e fechado ante a presença de micropoluentes selecionados - Pompei, Caroline Moço Erba (Universidade Estadual Paulista (Unesp), 2024)
The bioreactors used in the treatment of sanitary sewage contain a diverse community of microorganisms that establish associations with each other in a range of interactions. The culture of microalgae used in these bioreactors are responsible for recovering the nutrients contained in the effluent and their biomass is recovered at the end of the process to be used for different purposes. The potential of nutrient recovery, as well as the quality and quantity of bio compounds produced by microalgae, are closely related not only to the interactions between organisms, but also to the conditions of cultivation. The present project proposes to explore the composition of the bacterial and microalgae community by metabarcoding in a pitot scale raceway pond (open system) and flat panel photobioreactor (closed system), and to know if the presence of micropollutants (13 selected compounds) in the sewage to be treated could cause any change in terms of composition and interactions of the micro communities present in both bioreactors.
Composition and behavior of a consortium composed of microalgae and bacteria in open and closed biological reactors in the presence of selected micropollutants
Keywords: Microalgae; Metabarcoding; Sanitary sewage; DNA